Hubungan Pemakaian Sabun Pembersih Kewanitaan Dengan Terjadinya Keputihan Pada Wanita Usia Subur (WUS) Di Desa Karang Jeruk Kecamatan Jatirejo Kabupaten Mojokerto - Dyah Fitri Syuryandari , Zulfa Rufaida (LPPM Sekolah Tinggi Ilmu Kesehatan Majapahit Mojokerto, 2013)
One cause of vaginal discharge in women of childbearing age are wearing feminine cleansing Indonesia, 75% of women would have at least one time in the discharge can be caused by a miraculous. Whit womanhood factors such as pants that do not absorb, hygiene factor, purpose of this study was to determine the relationship using soap cleaning with the white female in fertile age women in the village of Karang Jeruk Country District Jatirejo Mojoker This type of research using correlational analytic cross sectional study design. Independent variable is soap white womanhood and the dependent variable. This study most fertile age women aged 18-45 years with a population of 252 people. Samples are taken using the technique Probability Sampling with Random sampling Cluster sampling as much as 154 women of childbearing age. The research was conducted in the village of Karang Jeruk Country district Jatirejo Mojokerto district on 7 May to 7 June 2012. The questionnaire research instruments. The results showed that nearly half of women of childbearing age use the soap as much as 60 female respondents (39%). And a fraction of the respondents had pathological vaginal discharge as much as 33 respondents (21.5%) and a small proportion of respondents having vaginal discharge physiological as much as 27 respondents (17.5%). Chi Square Test results found that the calculated results of X ² = 10.876 with α = 5% where X ² calculated> X ², which is 10.876> 3.481, so that means there is a relationship Hi accepted usage of soap with the occurrence of white womanhood. The strong relationship that is strong enough (0707) with a relative risk value of 0.24 times. The conclusion of this study was the age of Infertile Women who experience vaginal discharge caused by other factors including the cloth that does not absorb sweat, contraceptives, Hygiene factors (cleanliness) wipe the wrong way. Medical staff can give counseling of the way to avoid experience vaginal by using discharge can be overcome by using a clean water rinse from front to back, when using soap should female sex organs woman with a pH that is 3.5 to 5.5.